Immunocytochemical analysis of glucose transporter protein‐1 (GLUT‐1) in typical, brain invasive, atypical and anaplastic meningioma. Issue 1 (28th August 2014) - van de Nes, Johannes A. P.; Griewank, Klaus G.; Schmid, Kurt‐Werner; Grabellus, Florian
<x xml:space="preserve">Abstract</x> Glucose transporter‐1 (GLUT‐1) is one of the major isoforms of the family of glucose transporter proteins that facilitates the import of glucose in human cells to fuel anaerobic metabolism. The present study was meant to determine the extent of the anaerobic/hypoxic state of the intratumoral microenvironment by staining for GLUT‐1 in intracranial non‐embolized typical (WHO grade I; n = 40), brain invasive and atypical (each WHO grade II; n = 38) and anaplastic meningiomas (WHO grade III, n = 6). In addition, GLUT‐1 staining levels were compared with the various histological criteria used for diagnosing WHO grade II and III meningiomas, namely, brain invasion, increased mitotic activity and atypical cytoarchitectural change, defined by the presence of at least three out of hypercellularity, sheet‐like growth, prominent nucleoli, small cell change and "spontaneous" necrosis. The level of tumor hypoxia was assessed by converting the extent and intensity of the stainings by multiplication in an immunoreactive score (IRS) and statistically evaluated. The results were as follows. (1) While GLUT‐1 expression was found to be mainly weak in WHO grade I meningiomas (IRS = 1–4) and to be consistently strong in WHO grade III meningiomas (IRS = 6–12), in WHO grade II meningiomas GLUT‐1 expression was variable (IRS = 1–9). (2) Histologically typical, but brain invasive meningiomas (WHO grade II) showed no or similarly low levels of GLUT‐1 expression as observed in WHO grade I meningiomas (IRS = 0–4). (3) GLUT‐1 expression was observed in the form of a patchy, multifocal staining reaction in 76% of stained WHO grade I‐III meningiomas, while diffuse staining (in 11%) and combined multifocal and areas of diffuse staining (in 13%) were only detected in WHO grades II and III meningiomas, except for uniform staining in angiomatous WHO grade I meningioma. (4) "Spontaneous" necrosis and small cell change typically occurred away from the intratumoral capillary network embedded within the pattern of GLUT‐1 staining. Taken together, GLUT‐1 staining cannot be applied as a substitute for histologic grading in order to predict tumor behavior. However, assessment of tumor hypoxia in association with "spontaneous" necrosis and foci of small cell change may substantially contribute to the neuropathologic diagnosis of WHO grades II and III meningioma.